Implementasi Pengembangan Kurikulum Pendidikan Agama Islam Berbasis Inklusi di SD Tumbuh 2 Yogyakarta - Itmam Mutaqien; Dwi Ratnasari (ISLAMIKA, 2023)
The purpose of this study was to find out how the implementation of PAI curriculum development in SD grew 2 Yogyakarta. Researchers used qualitative methods and then the research data was obtained through observation, interviews and library analysis. Test the authenticity of the data through continuous observation and triangulation of sources and methods. The results of this study indicate: first: in planning before the learning activities begin, the curriculum coordinator and educators hold a Teacher At Work which will then have a discussion between the curriculum coordinator and the educators. Second; In its implementation, PAI curriculum development is focused on PAI teachers. As in elementary schools, the growth in teaching still refers to the national education curriculum which is adapted to the conditions of students. For the evaluation stage at the school, it is carried out periodically, namely every mid-semester and end of semester. Then the PAI evaluation process itself is carried out by the PAI teacher by adjusting the student's condition, for example in giving the task of practicing prayer, distinguishing normal students from those with disabilities.ions.